The use of non‐transplant biologics in solid organ transplant recipients: A practical review for the frontline clinician. Issue 7 (25th June 2022) - Szczepanik, Amanda; Choi, David; Brady, Beth; Chandran, Mary Moss; Diamond, Adam; Do, Vincent; Fredrick, Stacy; Kaiser, Tiffany; Khalil, Karen; Laub, Melissa R.; Leino, Abbie; Park, Jeong M.; et al.
Abstract: Biologics have become the forefront of medicine for management of autoimmune conditions, leading to improved quality of life. Many autoimmune conditions occur in solid organ transplant (SOT) recipients and persist following transplant. However, the use of biologics in this patient population is not well studied, and questions arise related to risk of infection and adjustments to induction and maintenance immunosuppression. Guidelines have been published highlighting management strategies of biologics around the time of elective surgical procedures, but this is not always feasible in urgent situations, especially with deceased donor transplantation. The aim of this review is to summarize the current literature regarding the use of these agents in solid organ transplant recipients, and specifically address induction and maintenance immunosuppression, as well as the need for alternative infective prevention strategies to create a practical reference for the frontline clinician, when faced with this complex clinical scenario.